Youth attitudes towards the use of virtual assistants and its relationship to self-confidence: A field study (Damascus University Journal of arts and humanities sciences, 2026)
This study aimed to identify young people's attitudes toward using virtual assistants and their relationship to self-confidence, as well as to determine the impact of variables such as gender, age, educational level, and duration of use on these attitudes. To achieve this objective, the study employed a descriptive-analytical approach, utilizing a social survey method with a sample. An electronic questionnaire, developed by the researcher, was used to measure attitudes toward using virtual assistants and self-confidence. The study sample consisted of 589 young people.The results showed that young people's attitudes toward using virtual assistants ranged from moderate to high across its three dimensions: cognitive, affective, and behavioral. The results also revealed a strong and statistically significant negative correlation between attitudes toward using virtual assistants and self-confidence, indicating that increased reliance on these technologies may reduce an individual's sense of competence and self-efficacy, and vice versa. Regarding the sample variables, the results did not show statistically significant differences based on gender or educational level. However, significant differences emerged based on age and duration of use, with attitudes being more positive among the 23-26 age group, particularly with moderate use of virtual assistants (one to three hours daily).At the end of the study, a set of recommendations was presented. The study emphasized the need to guide young people toward the conscious use of digital technologies, to integrate virtual assistants as supportive tools rather than replacements for their own abilities, and to conduct future research to broaden the understanding of the relationship between technology and the psychological and behavioral characteristics of young people.
Keywords: Attitudes; Youth; Virtual Assistants; Self-Confidence; Artificial Intelligence